Application Of the Popularity-Based Ranking Model in An Augmented Reality Web-Based Furniture Marketing Information System: Case Study at D Furniture Company - Sidik, Rais Akbar; Kusnandar, Toni; Putra, Yuda Purnama; Sambani, Egi Badar (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
Application of a Popularity-Based Ranking Model in a Web-Based Augmented Reality Furniture Marketing Information System: A Case Study of D FURNITUR. This marketing information system is essential for delivering pertinent information to consumers and aiding them in purchasing decisions. This research aims to develop a web-based furniture marketing information system incorporating Augmented Reality (AR) and a popularity-based ranking model, employing the Rapid Application Development (RAD) methodology, with D FURNITURE as the case study. The RAD technique was selected to expedite development and facilitate ongoing enhancement based on user feedback. The research encompasses system design and development phases, commencing with needs analysis via surveys and interviews with D FURNITURE management and potential users, culminating in system implementation. The resultant solution enables customers to visualize product designs online via an interactive interface augmented by AR. Prominent features encompass an augmented reality display of products in the user's surroundings, product selection informed by popularity rankings, and a cohesive ordering mechanism facilitated via WhatsApp. The findings yield tangible benefits through a robust and efficient furniture marketing information system, minimizing faults in product display, improving user experience in information retrieval, and augmenting satisfaction via a popularity-based rating system. Implementing the RAD approach facilitates flexible and adaptive development to meet future requirements.